Aktivitas Antioksidan Ekstrak Etil Asetat Daun Kelor (Moringa Oleifera L) - Kurang, Rosalina Yuliana; Koly, Faryda V Lamma; Kafolapada, Diana I (Journal of Pharmaceutical Care Anwar Medika (J-PhAM), 2020)
Moringa oliefera L is one of the most plants in Indonesia. One area has this plant is Alor island with the type of Moringa leaves are flavorful and not flavorful. The use of Moringa leaves is not widely known by the public. The aim of this research is to determine the antioxidant activity of moringa leaves flavorful. The method used is the extraction method and the DPPH method. The results of the analysis showed that ethyl acetate extract of Moringa oliefera L, contained compounds group of flavonoids, terpenoids and phenolic. Antioxidant activity test showed that the ethyl acetate extract of Moringa oliefera L have a strong antioxidant activity with an IC50 14,301 ppm.